The Gut Microbiome and Metabolome of Two Riparian Communities in the Amazon - Pires, Eder Soares; Hardoim, Cristiane Cassiolato Pires; Miranda, Karla Rodrigues; Secco, Danielle Angst; Lobo, Leandro Araújo; de Carvalho, Denise Pires; Han, Jun; Borchers, Christoph H.; Ferreira, Rosana B. R.; Salles, Joana Falcão; Domingues, Regina Maria Cavalcanti Pilotto; Antunes, Luis Caetano Martha (Frontiers in Microbiology, 2019)
During the last decades it has become increasingly clear that the microbes that live on and in humans are critical for health. The communities they form, termed microbiomes, are involved in fundamental processes such as the maturation and constant regulation of the immune system. Additionally, they constitute a strong defense barrier to invading pathogens, and are also intricately linked to nutrition. The parameters that affect the establishment and maintenance of these microbial communities are diverse, and include the genetic background, mode of birth, nutrition, hygiene, and host lifestyle in general. Here, we describe the characterization of the gut microbiome of individuals living in the Amazon, and the comparison of these microbial communities to those found in individuals from an urban, industrialized setting. Our results showed striking differences in microbial communities from these two types of populations. Additionally, we used high-throughput metabolomics to study the chemical ecology of the gut environment and found significant metabolic changes between the two populations. Although we cannot point out a single cause for the microbial and metabolic changes observed between Amazonian and urban individuals, they are likely to include dietary differences as well as diverse patterns of environmental exposure. To our knowledge, this is the first description of gut microbial and metabolic profiles in Amazonian populations, and it provides a starting point for thorough characterizations of the impact of individual environmental conditions on the human microbiome and metabolome.